2016
DOI: 10.17221/109/2015-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of rubberwood (Hevea brasiliensis) (Willd. ex A. Juss.) Müll. Arg. with maleic anhydride to prevent moulds

Abstract: ABSTRACT:The rubberwood samples were treated with 0.5-10% maleic anhydride (MA) solutions. The treatment of wood with 2.5% MA was adequate to prevent the growth of moulds on wood for 1 year at least. The viable count of Aspergillus niger van Tieghem PSU1 on MA treated wood indicated that fungal spores were not killed. The maleic anhydride treated wood slices had no antifungal activity. The concentration of MA released from treated wood in the leachate was 0.02 mg·m -3 . Agar well diffusion showed that the leac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…Based on these results, the stain fungi isolates that we obtained from the rubberwood are different from those found by OldertrØen et al (2016) which were Aspergillus niger, Aspergillus flavus, and Penicillium citrinum; and also different from those found by Razali et al (2016) which were Fusarium equiseti, Mucor irreguralis, and Lasiodiplodia theobromae. However, some results still showed similarities in genus level.…”
Section: Phylogenetic Of Stain Fungicontrasting
confidence: 92%
See 1 more Smart Citation
“…Based on these results, the stain fungi isolates that we obtained from the rubberwood are different from those found by OldertrØen et al (2016) which were Aspergillus niger, Aspergillus flavus, and Penicillium citrinum; and also different from those found by Razali et al (2016) which were Fusarium equiseti, Mucor irreguralis, and Lasiodiplodia theobromae. However, some results still showed similarities in genus level.…”
Section: Phylogenetic Of Stain Fungicontrasting
confidence: 92%
“…Valiante et al (2016) argued that discoloration is caused by pigmentation on the hyphae or melanin synthesis on the conidia during sporulation process. Previous studies reported that three stain fungi species were identified from rubberwood, which were Aspergillus niger, Aspergillus flavus, and Penicillium citrinum (Oldertrøen et al 2016). Meanwhile, Salman et al (2020) reported that at least there were two stain fungi isolated from air dried rubberwood which will be processed for furniture products in West Java Province, Indonesia, which were Aspergillus aflatoxiformans and A. foetidus.…”
Section: Introductionmentioning
confidence: 99%
“…The growth rate of fungus on the wood surface reached 90.5%. Meanwhile, Oldertrøen et al [19] found three stain-fungi species on rubberwood: Aspergillus niger, Aspergillus flavus, and Penicillium citrinum.…”
Section: Introductionmentioning
confidence: 99%
“…Stain fungi do not affect of strength loss, but decrease the aesthetic and cost of wood. Previous studies reported that three stain fungi were identified from rubberwood, which were Aspergillus niger, Aspergillus flavus, and Penicillium citrinum (Oldertrøen et al 2016). In fact, stain fungi were found to attack the part of piano produced by one company in Indonesia.…”
Section: Introductionmentioning
confidence: 99%